2010
DOI: 10.1002/mmce.20423
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on fractal frequency selective diaphragms in rectangular waveguide

Abstract: In this article, self-similarity and space-filling properties of fractal structures are explored as frequency selective diaphragms in rectangular waveguide, which can find applications in the design of compact, lightweight, and multiband waveguide filters with better out-of-band rejection ratio. Some self-affine fractal structures, based on Sierpinski gasket and plus shape fractals, are proposed, and the effect of scaling factor on the location of transmission bands is investigated. Self-similar structures lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The first FSS unit is a folded cross dipole, and the second one is composed of a large cross, four medium crosses, and 16 small crosses. Both FSS units can be regarded as the quasi‐fractal structures which provide a better compact and wideband performance for the FSS applications 20 . As it is shown in Luo et al 21 and Chatterjee and Parui, 22 the slotted FSS behaves as a bandpass spatial filter which allows in‐band signal to pass through and reflects the out‐of‐band signal.…”
Section: Design Of the Two Quasi‐amc Unitsmentioning
confidence: 99%
“…The first FSS unit is a folded cross dipole, and the second one is composed of a large cross, four medium crosses, and 16 small crosses. Both FSS units can be regarded as the quasi‐fractal structures which provide a better compact and wideband performance for the FSS applications 20 . As it is shown in Luo et al 21 and Chatterjee and Parui, 22 the slotted FSS behaves as a bandpass spatial filter which allows in‐band signal to pass through and reflects the out‐of‐band signal.…”
Section: Design Of the Two Quasi‐amc Unitsmentioning
confidence: 99%
“…Hilbert curve fractal structures have widely been used in the design of antennas, electromagnetic bandgap structures and as a transverse discontinuity in the rectangular waveguides [6][7][8]. It has been found that the Hilbert curve also shows a similar characteristic of negative permittivity and can be effectively used as the filter elements in the SIW technology.…”
Section: Introductionmentioning
confidence: 98%
“…We will consider both perfectly periodic and aperiodic systems. The last one is the fractal-like (Cantor-like) multilayer [29][30][31][32][33][34]. It is known that the periodicity disturbance of a layered isotropic one-dimensional sample produces appearing additional high-Q resonances (localized modes) in the stopbands.…”
Section: Introductionmentioning
confidence: 99%